LEGAL PROTECTION FOR BANK CUSTOMERS RELATED TO SAVINGS MONEY EMBEZZLED BY OFFICIALS AT BANK BRANCH HEADS - Nanda Yuliska; Benny Djaja (UNES Law Review, 2023)
The existence of a bank as a storage facility for public funds often creates legal problems which n essence can cause a loss to the customer. the existence of a bank which should be a forum for the community to store the funds they have. this s part of the bank's function n carrying out ts business sector n the banking sector because n practice there are legal problems experienced by customers with the nitials WE as eSport athletes. where the money n his savings was embezzled by the head of the Maybank branch with the nitials CA. based on this, the legal action that harms the customer s carried out by bank maybank n terms of the banking law, consumer protection law and Bank ndonesia Regulation Number 22/20/Pbi/2020 Concerning Bank ndonesia Consumer Protection article 7 paragraph (1) letter (e) that the Principles of Consumer Protection cover the protection of Consumer assets against misuse.